Writing and presenting reports - Eunson, Baden (Milton, Qld : John Wiley and Sons, 1994)
This book is about: Planning and structuring; Getting the facts: Secondary sources of data, Primary sources of data; Getting the picture; ...
Keywords: Report writing; Report writing